A study on recovery of metallic values from EAF flue dusts - (:unkn) unknown (My University, 2008)
The steelmaking industry which uses electric arc furnaces (EAF) generates approximately 250.000 tons of EAF flue dusts annually in Turkey. These flue dusts contain valuable metals such as zinc, iron and lead. For example, if these flue dusts can be treated efficiently, disposal problems certainly decreases and annually almost 40.000-75.000 tons of zinc can be recovered. In this study, powder and pellet forms of EAF flue dusts taken from a steel mill were carbothermally treated in a temperature controlled pilot scale rotary furnace via carbothermal reduction in order to investigate the reduction behavior of Zn and Pb. Temperature (900-1000 and 1100 °C) and time (0-90 minutes) were selected as reaction parameters. The chemical analysis was performed for the sample residues.
Keywords: Carbothermal; EAF dust; Lead; Recovery; Zinc